Coexistence of Ureaplasma and chorioamnionitis is associated with prolonged mechanical ventilation. Issue 1 (6th September 2016) - Jung, Euiseok; Choi, Chang Won; Kim, Su Yeong; Sung, Tae‐Jung; Kim, Haeryoung; Park, Kyoung Un; Kim, Han‐Suk; Kim, Beyong Il; Choi, Jung‐Hwan
Abstract: Background: Both histologic chorioamnionitis (HCAM) and Ureaplasma infection are considered important contributors to perinatal lung injury. We tested the hypothesis that coexistence of maternal HCAM and perinatal Ureaplasma exposure increases the risk of prolonged mechanical ventilation in extremely low‐birthweight (ELBW) infants. Methods: A retrospective cohort study was carried out of all ELBW infants born between January 2008 and December 2013 at a single academic center. Placental pathology and gastric fluid Ureaplasma data were available for all infants. Culture and polymerase chain reaction were used to detect Ureaplasma in gastric fluid. Prolonged mechanical ventilation was defined as mechanical ventilation that began within 28 days after birth and continued. Results: Of 111 ELBW infants enrolled, 84 survived beyond 36 weeks of postmenstrual age (PMA) and were included in the analysis. Eighteen infants (21.4%) had both HCAM and Ureaplasma exposure. Seven infants (8.3%) required mechanical ventilation beyond 36 weeks of PMA. Coexistence of HCAM and Ureaplasma in gastric fluid was significantly associated with prolonged mechanical ventilation after adjustment for gestational age, sex, mode of delivery, and use of macrolide antibiotics (OR, 8.7; 95%CI: 1.1–67.2). Conclusions: Coexistence of maternal HCAM and perinatal Ureaplasma exposure significantly increases the risk of prolonged mechanical ventilation in ELBW infants.